The detrimental effects of lead on human and animal health - Assi, Mohammed Abdulrazzaq; Mohd Hezmee, Mohd Noor; Haron, Abd Wahid; Mohd Sabri, Mohd Yusof; Rajion, Mohd Ali (Veterinary World, 2016)
Lead, a chemical element in the carbon group with symbol Pb (from Latin: Plumbum, meaning “the liquid silver”) and has an atomic number 82 in the periodic table. It was the first element that was characterized by its kind of toxicity. In animal systems, lead (Pb) has been incriminated in a wide spectrum of toxic effects and it is considered one of the persistent ubiquitous heavy metals. Being exposed to this metal could lead to the change of testicular functions in human beings as well as in the wildlife. The lead poising is a real threat to the public health, especially in the developing countries. Accordingly, great efforts on the part of the occupational and public health have been taken to curb the dangers of this metal. Hematopoietic, renal, reproductive, and central nervous system are among the parts of the human body and systems that are vulnerable toward the dangers following exposure to high level of Pb. In this review, we discussed the massive harmful impact that leads acetate toxicity has on the animals and the worrying fact that this harmful toxicant can be found quite easily in the environment and abundance. Highlighting its (Pb) effects on various organs in the biological systems, its economic, as well as scientific importance, with the view to educate the public/professionals who work in this area. In this study, we focus on the current studies and research related to lead toxicity in animals and also to a certain extent toward human as well.